2022
DOI: 10.1039/d2sc02074b
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde-functional thermoresponsive diblock copolymer worm gels exhibit strong mucoadhesion

Abstract: Optimizing the aldehyde content of thermoresponsive diblock copolymer worm gels via periodate oxidation leads to mucoadhesion performance comparable to that of chitosan (a gold standard positive control) in a fluorescence assay using porcine mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Recently, we reported that PAGEO5MA-functionalized diblock copolymer worm gels exhibit strong mucoadhesive behavior. 68 This is because the pendent aldehyde groups can react with the primary amine groups that are located at the surface of porcine urinary bladder mucosa. 68 Conversely, the corresponding PGEO5MA-functionalized diblock copolymer worm gels exhibit minimal mucoadhesion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that PAGEO5MA-functionalized diblock copolymer worm gels exhibit strong mucoadhesive behavior. 68 This is because the pendent aldehyde groups can react with the primary amine groups that are located at the surface of porcine urinary bladder mucosa. 68 Conversely, the corresponding PGEO5MA-functionalized diblock copolymer worm gels exhibit minimal mucoadhesion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…68 This is because the pendent aldehyde groups can react with the primary amine groups that are located at the surface of porcine urinary bladder mucosa. 68 Conversely, the corresponding PGEO5MA-functionalized diblock copolymer worm gels exhibit minimal mucoadhesion. In view of these observations, quartz crystal microbalance (QCM) experiments were performed to determine the extent to which a model globular protein (bovine serum albumin, BSA) interacts with (i) a PGEO5MA brush and (ii) the corresponding PAGEO5MA brush.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…More recent studies have synthesized aldehyde copolymers with mucoadhesion force to mucosa comparable to that of chitosan and other functional groups. 143,144 3.2. Viscoelasticity.…”
Section: T H Imentioning
confidence: 99%
“…Maleimide-functionalized PEGylated polymers such as alginate-polyethylene glycol-maleimide (Alg-PEGM) and poly­(lactide- co -glycolide)- block -polyethylene glycol-maleimide (PLGA-PEG-Mal) showed a propensity to aggregate with mucins and showed increased retention to the urinary bladder mucosa, respectively. , Acrylate-chitosan and polyethylene glycol diacrylate polymers have also been explored. , Similarly, methacrylate-functionalized materials have been demonstrated to exhibit enhanced adhesion to mucosal tissues. , Furthermore, designing copolymer hydrogels containing acrylate and methacrylate groups may strengthen mucoadhesion. , In addition, aldehyde-functionalized polymers have been known to enhance mucoadhesion. More recent studies have synthesized aldehyde copolymers with mucoadhesion force to mucosa comparable to that of chitosan and other functional groups. , …”
Section: Formulation Strategiesmentioning
confidence: 99%
“…20,21 Hydrogel-based drug delivery systems were elaborated with the aim of intravesical administration. 22,23 Particular attention is paid to emulsion systems intended for intravesical drug delivery due to their ability to immobilize both hydrophobic and hydrophilic molecules. 24−27 Mucoadhesive emulsions are of increasing interest given the combination of properties which are beneficial for intravesical drug delivery.…”
Section: Introductionmentioning
confidence: 99%